A Narrative Review of The Effects of Mobile Intervention on Pregnant Women with Depression - Hidayati, Nur Oktavia; Nurhidayah, Ikeu; Mufaj, Elda Nurfadila; Prawesti, Sabrina Junieta; Fadilah, Tria Nurhayyu; Ramdhona, Dinyatul Arba (Prosiding Seminar Nasional Keperawatan Universitas Muhammadiyah Surakarta, 2023)
Pregnancy is one of the events that every woman experiences before becoming a mother. Many physiological and psychological changes occur in the mother's body during this time. As a result, the mother and fetus suffer from a variety of unfavorable consequences, one of which is depression. Although doctors usually believe antidepressant medicines to be safe for severe depression, most pregnant women are hesitant to use them for fear of negative effects. The purpose of this study is to see how mobile treatments affect pregnant women who are depressed. The narrative review approach is used in this literature study. Search PubMed, EBSCO, and Science Direct databases for papers containing the keywords pregnant women, pregnancy, depression, and mobile intervention with inclusion criteria, such as articles published within the previous 10 years, forms of experimental study, in English, and full-text. Seven final papers were obtained as the number of final articles appropriate for evaluation. The findings of an analysis of seven studies on mobile interventions to reduce the prevalence of depression in pregnant women reveal a substantial decrease. Because mobile intervention is successful in lowering the prevalence of depression in pregnant women, it is advised that it be used as an alternative in delivering the intervention to pregnant women, particularly in situations of depression.